2010
DOI: 10.1203/pdr.0b013e3181ed17e4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GATA6 Sequence Variants in Patients With Congenital Heart Defects

Abstract: ABSTRACT:Although the etiology for the majority of congenital heart disease (CHD) remains poorly understood, the known genetic causes are often the result of mutations in cardiac developmental genes. GATA6 encodes for a cardiac transcription factor, which is broadly expressed in the developing heart and is critical for normal cardiac morphogenesis, making it a candidate gene for congenital heart defects in humans. The objective of this study was to determine the frequency of GATA6 sequence variants in a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 32 publications
2
65
0
3
Order By: Relevance
“…Biochemical analysis demonstrated that the GATA6 A178V mutant protein resulted in increased transactivation ability for cardiac genes compared with the wildtype. Our first report and subsequent reports by Maitra et al 4 and Lin et al 2 in this issue provide an approach for the etiology of nonsyndromic or 'multi-factorial' CHD in the post-genomic era, and together indicate that mutations in GATA6 cause CHD implicated in the cardiac OFT and septal development.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Biochemical analysis demonstrated that the GATA6 A178V mutant protein resulted in increased transactivation ability for cardiac genes compared with the wildtype. Our first report and subsequent reports by Maitra et al 4 and Lin et al 2 in this issue provide an approach for the etiology of nonsyndromic or 'multi-factorial' CHD in the post-genomic era, and together indicate that mutations in GATA6 cause CHD implicated in the cardiac OFT and septal development.…”
mentioning
confidence: 58%
“…Another recent study by Maitra et al showed two novel sequence variations in GATA6 (A178V and L198V) from the screening of 310 individuals with CHD. 4 These variants were identified in two individuals, one with tetralogy of Fallot and another with atrioventricular septal defect, but not in 288 ethnically matched healthy controls. Biochemical analysis demonstrated that the GATA6 A178V mutant protein resulted in increased transactivation ability for cardiac genes compared with the wildtype.…”
mentioning
confidence: 96%
“…Мутации в гене NOTCH1 (9q34-35) ведут к патологии передачи информации, рисунок 1 -Схематическое изображение анатомических границ патологии, сочетанных с ДАК (розовым цветом отмечены структуры, подверженных патологии) которые ответственны не только за формирование ДАК, но и за ускоренный процесс кальцификации створок клапана (таблица 1) [23,24]. Мутации в факторе транскрипции GATA6 были ассоциированы с врожденными пороками сердца, включая тетраду Фалло, общий артериальный ствол, дефект межпредсердной перегородки [25,26]. Ген GATA6 участвует во внутриутробном формировании выходного тракта и деление данного гена в клетках нервного гребня у мышей приводит к внутриутробной летальности, вследствие спектра патологий со стороный дуги аорты и внутрисердечных дефектов [27].…”
Section: генетикаunclassified
“…The etiology of TOF is multifactorial, implying contributions from sequence variations, anomalous gene expression, and epigenetic factors, as well as environmental contributions. Functional mutations of several important cardiac-related transcriptional factor genes and chromosomal abnormality were identified in patients with TOF, supporting a genetic contribution (4)(5)(6). In spite of the expanding knowledge of the genetic mechanisms involved in cardiac formation, there remain nearly 80% of children with congenital heart defects who do not have a known genetic defect.…”
mentioning
confidence: 93%